PENGARUH PEMOTIVASIAN TERHADAP EFEKTIVITAS PENGELOLAAN KERUMAHTANGGAAN DI BAGIAN UMUM SEKRETARIAT DAERAH KOTA TASIKMALAYA - Astri Siti Fatimah (Jurnal Administrasi Publik, 2016)
Based on the results of the study found the low effectiveness of the management ofkerumahtanggaan of them in administrating as well as an inventory of equipment/goods in theGeneral section of the Secretariat of the environmental areas such as the preparation of KIB,the provision of food and drink, preparation of site, preparation of equipment/supplies (seats,sound system, etc) for the purposes of meetings/conferences/activities are limited, and thepreparation of a plan of work programmes and activity Sub. Part of the household due to thelarge number of routine activities that must be implemented. This happens becausepemotivasian has not been solely implemented.The research method used is descriptive analysis. Data collection techniques usedthrough the study of librarianship and field studies that consists of: 1) observation (directobservation against the object of the research); 2) interviews; 3 now).Based on the research results and discussion can be expressed pemotivasian that theempirical basis have been shown to provide significant effects against the effectiveness of themanagement of kerumahtanggaan in the General section of the Secretariat of the regional townof Tasikmalaya, either partially or simultaneous. The magnitude of the influence of thepemotivasian against the effectiveness of the management of kerumahtanggaan in the Generalsection of the Secretariat of the regional city of Tasikmalaya reflected the magnitude of theinfluence of dimensions pemotivasian that are teoritik basic dimensions include wake up to, principles of communication, the principle of recognition, the principle of authority delegated,principles of fair and decent as well as the dimension of the principle of reciprocal attention.